A Network Analysis of Sexually Transmitted Diseases and Online Hookup Sites Among Men Who Have Sex With Men. Issue 7 (July 2018) - Chan, Philip A.; Crowley, Christina; Rose, Jennifer S.; Kershaw, Trace; Tributino, Alec; Montgomery, Madeline C.; Almonte, Alexi; Raifman, Julia; Patel, Rupa; Nunn, Amy
Abstract : Background: Sexually transmitted diseases (STDs) are increasing among gay, bisexual, and other men who have sex with men (MSM). Little is known about the use of websites and mobile phone applications to meet sexual partners ("hookup sites") and association with STD diagnoses. Methods: We performed a demographic and behavioral assessment of 415 MSM presenting to the Rhode Island STD clinic. Bivariate and multivariable analyses assessed associations between using hookup sites and testing positive for syphilis, gonorrhea, or chlamydia. Venue-based affiliation networks were created to evaluate hookup sites and their association with STD diagnoses. Results: Among 415 MSM, 78% reported meeting a partner online in the last 12 months, and 25% tested positive for at least one STD. Men who met partners online were more likely to be white (67% vs. 54%, P = 0.03) and have more than 10 lifetime partners (87% vs. 58%, P < 0.05). The most commonly used hookup sites included Grindr (78%), Scruff (35%), and Tinder (22%). In the multivariable analysis, only Scruff use was associated with testing positive for an STD (odds ratio, 2.28; 95% confidence interval, 1.09–4.94). However, among men who met partners online, 75% of men diagnosed as having an STD had met a sexual partner on Grindr, including 100% of those who were diagnosed as having gonorrhea. Conclusions: Use of hookup sites was nearly ubiquitous among MSM undergoing STD screening. Specific hookup sites were significantly associated with STD diagnoses among MSM. Greater efforts are needed to promote STD screening and prevention among MSM who meet partners online. Abstract : Most men who have sex with men surveyed at a sexually transmitted disease (STD) clinic reported using an online application (hookup site) to find sex partners. Use of specific hookup sites may increase risk of an STD diagnosis. However, widespread use of hookup sites offers opportunities for STD screening and prevention messaging.